Perencanaan Sistem Plambing Air Bersih dan Air Buangan di Rusunami X dengan Aspek Konservasi Air - Amda Rahman; Eka Wardhani; Nico Halomoan (Jurnal Serambi Engineering, 2021)
Flat X will be built to meet the demand for  simple and affordable homes  in Sumedang Regency. The construction of an apartment must be equipped with adequate plumbing for clean water and wastewater so  that the health of the residents is maintained. The purpose of this research is to plan the need for clean water, including the calculate dimensions of the  groundwater reservoir , roof reservoir,  and clean water pipe  and calculate  wastewater discharges ( grey  and black water) and calculate the use  of greywater recycling.  Recycled water is used in the rinsing  and watering of plants. Research  results for   a flat population that can reach  3,658 people, the total requirement for  clean water which  is 311 m3/day, the volume of underground reservoir  1 and 2 each 352 m3 and 165 m3. The volume of roof reservoir  1 and 2 is  42 m3 and 34 m3, respectively. The diameter of the r first class clean water pipe has a range of 20-25 mm, the diameter of the  second class clean water pipe has a range of 25-25 mm, pipe diameter greywater has a range from  48-60 mm, pipe diameter black water range 48-114 mm. Greywater treatment is carried out using a Sewage Treatment Plant (STP) which has a volume of 200 m3. The results of the treatment efficiency  are 80%, so the recycling process is capable of  saving  51% of clean water.